Evaluation of characteristics of Pediococcus spp. to be used as a vaginal probiotic - Borges, S. (2014)
The aim of our research was to select, identify and characterize an isolate of lactic acid bacteria to be considered as a vaginal probiotic. Methods and Results: Thirty-five isolates of Pediococcus spp. showed bacteriocinogenic activity against Listeria monocytogenes and the ability to survive in simulated vaginal fluid (SVF) at pH 4!2. One isolate of Pediococcus spp. was selected and characterized to evaluate its safety before the use as vaginal probiotic. Pediococcus pentosaceus SB83 did not show the presence of virulence factors such as the production of gelatinase, lipase and DNase, haemolytic activity, nor the presence of virulence genes (genes esp, agg, gelE, efaAfm, efaAfs, cylA, cylB and cylM). Pediococcus pentosaceus SB83 was considered sensitive to chloramphenicol, gentamicin, streptomycin, kanamycin, erythromycin and ampicillin. This strain was considered resistant to tetracycline and vancomycin. Pediococcus pentosaceus SB83 was a biofilm producer at different pH values (4!2, 5!5 and 6!5) in SVF and in de Man, Rogosa and Sharpe medium. Conclusions: The in vitro results provide a basis for the use of P. pentosaceus SB83 as a vaginal probiotic, to prevent colonization by L. monocytogenes in pregnant women. Significance and Impact of Study: The application of vaginal probiotics could have the potential for preventing vaginal infections and consequently reduce abortion and neonatal infections.